Analysis Of The Factors Of Difficulties Factors Of Economic Education Students In Completing Thesis - Viona Pardila Br. Sembiring; Sanggam Pardede; Dearlina Sinaga (STABN RADEN WIJAYA WONOGIRI, 2023)
The phenomenon underlying this study is the delay of Economics Education students at HKBP Nommensen University Medan in completing their theses, influenced by both internal and external factors. This research aims to analyze the factors causing students' difficulties in the thesis writing process. The study employed a descriptive qualitative method using interviews, observation, and documentation, with data analyzed through reduction, display, conclusion drawing, and triangulation. The findings indicate that internal factors include limited intellectual ability in constructing logical arguments, low achievement motivation, and weak understanding of research methodology. External factors involve inflexible university policies, limited facilities, a curriculum that does not fully support research needs, and less optimal supervision from lecturers. These results emphasize that thesis completion obstacles arise from a combination of individual and academic system aspects, thus requiring improvements from both sides.